Sustainable feminisms - Sarker, Sonita, 1961- (Amsterdam ; Boston : Elsevier JAI, 2007)
This volume illuminates the encounter of feminist activism with scholarship in political science, cultural studies, sociology, ethnic studies, and economics. The essays contribute images of the forces that lead to the development of many different kinds of feminisms and womens movements across the globe in the 20th century and recently. They explore the cultural constructions and legitimations of sustainability during the processes through which various agents interpret the relevance of feminisms for their social and political initiatives. The volume offers new dimensions on the relationships across time and place among activisms and scholarships, as ways to contemplate how feminisms are sustainable and whether there is a future beyond sustainability. This book gives a genealogical account of various different kinds of feminisms. It offers new dimensions on the relationships across time and place among activisms and scholarships. It investigates and discusses how feminisms are sustainable.
Introduction: sustainable feminisms / Sonita Sarker -- The female body: practice and metaphor across the Maya-'American'continuum / Janferie Stone -- Caring for survival: motherwork and sustainable feminisms / Leah Schmalzbauer, Alice Verghese, Meenu Vadera -- Hailing the "authentic other": constructing the Third World woman as aid recipient in donor NGO agendas / Chilla Bulbeck -- From global to local feminisms: transnationalism, foreign aid and the women's movement in Ukraine / Alexandra Hrycak -- Sacrifice, abandonment, and interventions for sustainable feminism(s): the non-profit industrial complex and transborder substantive democracy / Anna M. Agathangelou, Tamara L. Spira -- The Anarcha Project: performing in the medical plantation / Petra Kuppers -- Sustainable networking: collaboration for women's human rights activists, scholars, and donors / Brooke Ackerly.
Description based on print version record.
Keywords: Feminism; Sustainable development; Women in development; Feminism & feminist theory; Social Science -- Feminism & Feminist Theory